iBABY CLOUD: SHAPING THE FUTURE OF PREGNANT WOMEN USING IOT - M. Sowmiya; Princy , V.Dorathy; R.Kiruthica; R.Monisha; B.Prajwala (International Journal of Psychosocial Rehabilitation, 2020)
Promoting healthy pregnancy and safe childbirth is a goal of all Indian health care systems. Despite significant improvements in recent decades, mothers and their babies are still at risk during the prenatal period, which covers pregnancy, delivery, and the postpartum. Babies born too early are more likely to die than those born at term. To improve prenatal health, we need the right tools to assess problems and their causes. We also need to monitor the health condition of the pregnant woman frequently. We have proposed the system using IOT which is based on maternal health care solution that promises to effectively monitor the health of the pregnant women in rural India. This system allows sensing various attributes like the temperature, heart rate and the blood pressure of the mother frequently. The readings of the attributes are stored in a cloud. In case of any abnormal conditions there is a message which is sent to the hospital, doctor in charge and the guardian of the patient. We have also used Diffie Hellman Key Exchange algorithm to secure transmission of data.